Arm in arm : the Grimké sisters' fight for abolition and women's rights - Carpenter, Angelica Shirley (Zest Books, 2025)
"Sisters Sarah and Angelina Grimké grew up in wealth and privilege in early nineteenth century Charleston, South Caroline. Following the standards of the time, they should have known nothing but prosperity, high social status, and Southern gentility for all their lives. But neither could look away from the inhumanity, violence, and cruelty of the enslavement they saw everywhere, even in their own home. Shaped by their religious beliefs and a fierce sense of compassion, the sisters moved north to begin a fight that would change America forever. Historian and author Angelica Shirley Carpenter tells the remarkable true story of the sisters' lives as they cut a swath across the northeastern United States, speaking out against slavery even while facing violence from pro-slavery mobs. When women were expected to stay at home and be quiet, they spoke up, too, for women's rights, becoming pioneer advocates for that civil liberties movement. Sarah and Angelina's activism played an important role in the early 1800s, and their actions have had lasting effects--influencing figures such as Ruth Bader Ginsberg--that have set the stage for present-day crusades for equality"--